2019
DOI: 10.1038/s41598-019-42563-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of childhood trauma and brain-derived neurotrophic factor Val66Met polymorphism on posttraumatic stress symptoms and cortical thickness

Abstract: Interaction between childhood trauma and genetic factors influences the pathophysiology of posttraumatic stress disorder (PTSD). This study examined the interaction effect of childhood trauma and brain-derived neurotrophic factor (BDNF) Val66Met polymorphism on PTSD symptoms and brain cortical thickness. A total of 216 participants (133 healthy volunteers and 83 PTSD patients) were recruited. T1-weighted structural magnetic resonance imaging, BDNF rs6265 genotyping through blood sampling, and clinical assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 91 publications
2
21
0
Order By: Relevance
“…Genetic studies for PTSD are useful to identify risk factors for the development of the disorder and improve its treatment 20 , and BDNF is considered a relevant candidate gene for PTSD [6][7][8]21 . Supporting this, previous studies have shown that Met allele carriers of the BDNF Val66Met polymorphism, compared to Val/Val homozygotes, www.nature.com/scientificreports www.nature.com/scientificreports/ have impaired fear extinction learning 18 and poorer response to exposure therapy 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies for PTSD are useful to identify risk factors for the development of the disorder and improve its treatment 20 , and BDNF is considered a relevant candidate gene for PTSD [6][7][8]21 . Supporting this, previous studies have shown that Met allele carriers of the BDNF Val66Met polymorphism, compared to Val/Val homozygotes, www.nature.com/scientificreports www.nature.com/scientificreports/ have impaired fear extinction learning 18 and poorer response to exposure therapy 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The SNP in the gene BDNF, BDNFVal66Met, is one example, among many, of an interesting candidate to explore for influencing chemotherapeutic impact and secondary effects across development. This SNP in the BDNF gene has been associated with altered susceptibility to a variety of neuropsychiatric disorders including anxiety and depression in adults (Frielingsdorf et al, 2010; Gatt et al, 2009; Gratacos et al, 2007; Jiang et al, 2005; Momose et al, 2002; Sen et al, 2003; Sklar et al, 2002; Ventriglia et al, 2002) and more recently has been shown to influence PTSD symptoms and cortical thickness in childhood trauma (Jin et al, 2019). This valine-to-methionine substitution at position 66 of the BDNF prodomain alters normal interactions with the sorting protein, sortilin, resulting in altered trafficking of BDNF into the regulated secretory pathway, which leads to an approximate 30% decrease in activity-dependent release (Chen et al, 2005, 2006; Chen et al, 2004; Egan et al, 2003).…”
Section: Genetic Influences To Consider For Effects Of Cancer Treatmementioning
confidence: 99%
“…One way to alleviate the clinical heterogeneity of PTSD is to take advantage of intermediate phenotypes, especially the quantitative neuroimaging phenotypes [26][27][28] . A growing body of imaging genetics research has proven the association between neuroimaging measures and candidate genes in PTSD [29][30][31] . Catechol-O-methyltransferase (COMT) Val 158 Met (rs4680) and brain-derived neurotrophic factor (BDNF) Val 66 Met (rs6265) polymorphisms are two typical and well-described genetic variants that have been proven to be associated with stress response and resilience [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Catechol-O-methyltransferase (COMT) Val 158 Met (rs4680) and brain-derived neurotrophic factor (BDNF) Val 66 Met (rs6265) polymorphisms are two typical and well-described genetic variants that have been proven to be associated with stress response and resilience [32][33][34] . These two genetic variants have been extensively investigated in populations consisting of healthy subjects 33,35 and those with anxiety disorders 36,37 , including PTSD 29,31 . Meanwhile, both COMT rs4680 and BDNF rs6265 regulate the brain dopamine system 38 -an important system in the pathogenesis of PTSD-by their important role in regulating fear memory emotion and behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation